Potential strategies for increasing drug-discovery productivity. (April 2014) - Cumming, John G; Finlay, M Raymond V; Giordanetto, Fabrizio; Hemmerling, Martin; Lister, Troy; Sanganee, Hitesh; Waring, Michael J
The productivity challenge facing the pharmaceutical industry is well documented. Strategies to improve productivity have mainly focused on enhancing efficiency, such as the application of Lean Six Sigma process improvement methods and the introduction of modeling and simulation in place of 'wet' experiments. While these strategies have their benefits, the real challenge is to improve effectiveness by reducing clinical failure rates. We advocate redesigning the screening cascade to identify and optimize novel compounds with improved efficacy against disease, not just with improved potency against the target. There should be greater use of disease-relevant phenotypic screens in conjunction with target-based assays to drive medicinal chemistry optimization. An opportunistic approach to polypharmacology is recommended. There should also be more emphasis on optimization of the molecular mechanism of action incorporating understanding of binding kinetics, consideration of covalent drug strategies and targeting allosteric modulators.